2001
DOI: 10.1007/s004420100766
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of a cladoceran (Daphnia galeata) and a calanoid copepod (Eodiaptomus japonicus) on algal and microbial plankton in a Japanese lake, Lake Biwa

Abstract: Macrozooplankton may affect algal and microbial plankton directly through grazing or predation and indirectly through nutrient regeneration. They may also affect potential prey positively by removing alternative predators. Here, we examined the effects of a cladoceran (Daphnia) and a calanoid copepod (Eodiaptomus) on algal and microbial plankton in a Japanese lake using in situ experiments in which we manipulated the nutrient supply and biomass of these macrozooplankton. The response of algal and microbial pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
38
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 55 publications
5
38
0
Order By: Relevance
“…Aliquots of lake water were fixed with 0.4% acid Lugol to determine initial cell numbers of phytoplankton species. Macrozooplankton, mainly D. galeata and E. japonicus, were collected by vertical tows of a conical net with a 300-µm mesh from 15 m depth to the surface, concentrated, rinsed, and used as we report elsewhere (Yoshida et al 2001b).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Aliquots of lake water were fixed with 0.4% acid Lugol to determine initial cell numbers of phytoplankton species. Macrozooplankton, mainly D. galeata and E. japonicus, were collected by vertical tows of a conical net with a 300-µm mesh from 15 m depth to the surface, concentrated, rinsed, and used as we report elsewhere (Yoshida et al 2001b).…”
Section: Methodsmentioning
confidence: 99%
“…For the sample of phytoplankton, 500 ml of the 200-µm filtrate was fixed as above and stored in the dark. Macrozooplankton in the bottles were counted under a dissecting microscope and their biomass was estimated (Yoshida et al 2001b). Phytoplankton in the 500-ml samples were concentrated to 20 ml by sedimentation for at least 4 days, and counted under a microscope in a 1-ml Sedgwick-Rafter chamber at 40-200× magnification.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gilbert (1985Gilbert ( , 1988b and Schneider (1990) demonstrated that two mechanisms are at work in these interactions: exploitative competition and interference competition. However, it is unlikely that exploitative competition was a factor in our experiment be- Yoshida et al (2001) cause an abundance of C. vulgaris was supplied in the tanks. Therefore, it seems likely that rotifers were out-competed by Daphnia primarily through interference competition (that is, through damage incurred by being swept into the branchial chambers of Daphnia), which apparently is more important than exploitative competition in the interaction between Daphnia and rotifers (Williamson 1987, Gilbert 1988a, Ronneberger et al 1993).…”
mentioning
confidence: 94%